INTRACYSTIC PAPILLARY CARCINOMA OF THE BREAST: CASE REPORT - Ebru Şen Oran; Nesimi Mecit; Zerrin Calay; Şefik İğdem; Gürsel Soybir (European Journal of Breast Health, 2010)

(untitled)
Intracystic papillary carcinoma which has a better prognosis than ductal carcinoma is a rare tumor of breast. A 50-year-old female was admitted to hospital with palpable mass on her left breast, which was mainly a cystic lesion including a solid component, with regular margin, and 2.5 cm in dimension on ultrasound examination. Fine needle aspiration biopsy of the solid component of 1.3 cm inside the cyst showed proliferative papillary structures with atypia. The patient underwent segmental mastectomy. Papillary carcinoma was detected on frozen section examination and sentinel lymph node biopsy was applied due to the doubt of invasive carcinoma. Intracystic papillary carcinoma was ascertained on postopertive histopathological examination. Intracystic papillary carcinoma should be recalled in the evaluation and diff erantial diagnosis of cystic lesions detected on postmenopausal women. Segmental mastectomy is suggested in the treatment of intracystic papillary carcinoma. However, there is no consensus as to performing sentinel node biopsy and adjuvant therapy.